(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The main purpose of the article lies with the Vietnam War literature that has passed through several distinct phases. It will show how this war and its repercussions have been the central theme of Philip Roth’s writings. Without any doubt, generations of future historians will puzzle over the complexities of the Vietnam controversy. There are issues of local, national, and international significance, now intermixed, which will have to be untangled and studied in the light of history’s perspective. Underneath these popular issues which daily exacerbate the press and the politicians, historians of the future may find several facets which have not received contemporary attention, and which deserve penetrating examination.